2015
DOI: 10.1021/acs.est.5b02781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Toxic Leachate from Commercial Plastics on Larval Survival and Settlement of the Barnacle Amphibalanus amphitrite

Abstract: Plastic pollution represents a major and growing global problem. It is well-known that plastics are a source of chemical contaminants to the aquatic environment and provide novel habitats for marine organisms. The present study quantified the impacts of plastic leachates from the seven categories of recyclable plastics on larval survival and settlement of barnacle Amphibalanus (=Balanus) amphitrite. Leachates from plastics significantly increased barnacle nauplii mortality at the highest tested concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(108 citation statements)
references
References 60 publications
7
98
0
3
Order By: Relevance
“…Here, migrates from PVC and PUR induced the highest acute toxicity compared to other commodity plastics in the freshwater cladoceran Daphnia magna, 54 the marine copepod Nitocra spinipes, 55 and the barnacle Amphibalanus amphitrite. 56 PVC and PUR are known to require large numbers and quantities of additives and have been ranked most hazardous based on their chemical composition. 57 Notably, all PLA products induced strong baseline toxicity similar to PVC and PUR.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Here, migrates from PVC and PUR induced the highest acute toxicity compared to other commodity plastics in the freshwater cladoceran Daphnia magna, 54 the marine copepod Nitocra spinipes, 55 and the barnacle Amphibalanus amphitrite. 56 PVC and PUR are known to require large numbers and quantities of additives and have been ranked most hazardous based on their chemical composition. 57 Notably, all PLA products induced strong baseline toxicity similar to PVC and PUR.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…1 Previous studies have described acute toxicity of leachable fractions of various plastic types toward Daphnia magna 17,18 and the marine copepod Nitocra spinipes. 19 Li et al (2016) 20 revealed larval toxicity and settlement inhibition to the barnacle Amphibalanus amphitrine during a 24 h exposure scenario in leachates from seven recyclable commercial plastic products. Cytotoxic end points like cell growth, survival and colony-forming capability were negatively affected by plastic leachates from biomedical devices tested in the human cell line L929 after 1 h of exposure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For nanomaterials, mostly ions are released, such as Zn 2+ or Co 2+ from zinc oxide (ZnO) or tungsten carbide–cobalt (WC‐Co) nanoparticles, respectively (e.g., Kühnel et al ). For MP, the leaching of soluble additives shows an equivalent dissolution effect, and impact on organisms has been demonstrated by Bejgarn et al () and Li et al (). However, exposing organisms to a mixture of particles and dissolved substances results in difficulties in the evaluation of toxicity tests because the bioavailability and uptake kinetics of particles and plastic‐derived chemicals into organisms may differ.…”
Section: Microplastic Particles: Sample Preparation In Liquid Mediamentioning
confidence: 73%